POTENSI DAN KEBIJAKAN PENGEMBANGAN KEPARIWISATAAN DI KABUPATEN GIANYAR - Ari Surya Wibawa, Dewa Gde; Anom Pemayun, Cok Istri (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013)
Gianyar regency is one of the regencies in Bali which is well known by tourists both foreigner people; it has 59 objects in the form of ancient tourisms, nature tourisms. As it is known that tourism sector is the superior sector in Gianyar regency, than it must have an important component in increasing territory revenue. However, in the implementation, the Department of Tourism found some obstacles in practice, such as incomplete infrastructures. This study using empirical legal research method, than the source of data is field research as the primary data and library research as secondary data. Data analysis techniques used in data processing is qualitative technique, and then the data is analyzed; furthermore, it is presented in analytical descriptive. The conclusion is that Gianyar regency has a great tourism potential and it has tourisms attractive, with the policy of tourism development through the implementation of seven-charm.
Keywords: Tourism Development, Implementation of Seven-Charm, and Tourism Components